Development of a Multimedia Learning Module (MLM) Based on Local Wisdom of the Banga Welu Game to Increase Student Motivation in Physics Learning - Gusemanto, Theofiulus Gratiamus; Hidayatullah, Zul (Pendidikan Fisika FITK UIN Sunan Kalijaga, 2023)
This research aims to: (1) produce a multimedia learning module (MLM) based on the local wisdom of the Banga Welu game that is suitable and valid for use in learning, and (2) determine the effectiveness of a multimedia learning module (MLM) based on the local wisdom of the Banga Welu game in increasing motivation students in learning physics. This research is included in Research & Development (R&D) research according to the development design from 4D. The research design used in product trials is a pretest-posttest control group design. The subjects in this research consisted of 104 instrument and product testing students. Product validation was carried out using an ideal standard score (Sbi) and General Linear Model (GLM) with a significance level of 0.05 to test the product's effectiveness in increasing students' motivation in learning physics. The validation results of the validators show that the multimedia learning module (MLM) based on the local wisdom of the Banga Welu game is very suitable for use both in terms of the media aspect and the material aspect contained in it. The GLM with effect size result of students' physics learning motivation is 0.242 and is in the medium category. The results of this effect size test show that the multimedia learning module based on the local wisdom of the Banga Welu game effectively motivates students to learn physics.